Temperature influence on leaf crinkle disease expression in urdbean (Vigna mungo (L.) Hepper) and potential distribution of the disease in India. (June 2019) - Dubey, A.K.; Sinha, P.; Baranwal, V.K.; Mishra, S.; Saritha, R.K.
Abstract: Blackgram or urdbean ( Vigna mungo (L.) Hepper) and mungbean ( Vigna radiata (L.) Wilczek) are important leguminous crops of India, Pakistan and South-East Asian Countries. India accounts largest acreage but productivity is very low due to prevalence of biotic stresses. Among the biotic stresses, Urdbean Leaf Crinkle Disease (ULCD) is considered to be one of the most serious diseases and causes yield loss up to 100%. Symptom expression was observed to be highly influenced by temperature. Threshold temperatures for symptoms expression were determined through mechanical inoculation of seeds and exposure to fixed temperature under glasshouse conditions. Typical ULCD symptoms were observed in the temperature range 25–38 °C. Disease incidence was significantly increased between temperature range 30–35 °C and reduced at 38 °C or above. Effect of temperature on ULCD was fitted to a non-linear beta model. Based on the model potential ULCD distribution has been predicted. It was evidenced that northern India and part of central India is prone to severe leaf crinkle disease during June–September (kharif season). However, disease incidence appeared to be low during March–May (summer season) crop. Predicting potential geographical areas for low disease incidence is an important component in strategic management of the disease under changing climates. Highlights: Urdbean leaf crinkle disease (ULCD) development in blackgram is highly influenced by temperature. Typical ULCD symptoms were observed in the temperature range 25–38 °C with maximum incidence at about 30–32 °C. Predicting potential locations for low or no disease incidence is an important component in strategic disease management.